2019
DOI: 10.1101/585935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of a caries preventive intervention in remote Indigenous Australian children

Abstract: IMPORTANCE: The burden of dental caries in remote Indigenous communities in Australia is unacceptably high. OBJECTIVES: We tested the impact of an annual caries preventive intervention, delivered by a fly-in/fly-out professional team, on Indigenous children residing in a remote Australian community, involving selective fissure sealants, topical povidone iodine and fluoride varnish application. The outcome was caries increment at 12- and 24-month follow-up. DESIGN, SETTING, PARTICIPANTS: Around 600 Indigenous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…This is consistent with our baseline study where caries experience was approximately twice in those with higher counts of salivary MS than those with lower counts [33], demonstrating that simple chair side assessment of microbial loads would assist in determining the risk for future caries. Furthermore, preventive interventions to reduce the bacterial loads were found to be equally effective in this community [34] and advanced investigations suggested that this could be due to a reduction of oral microbial diversity as a result of improved oral health of the children [23].…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with our baseline study where caries experience was approximately twice in those with higher counts of salivary MS than those with lower counts [33], demonstrating that simple chair side assessment of microbial loads would assist in determining the risk for future caries. Furthermore, preventive interventions to reduce the bacterial loads were found to be equally effective in this community [34] and advanced investigations suggested that this could be due to a reduction of oral microbial diversity as a result of improved oral health of the children [23].…”
Section: Discussionmentioning
confidence: 97%